Aerodynamic study of combustor using axial swirler - Mohammad Nazri, Jaafar; M. K. F., M. Nor; Mohamad Shaiful Ashrul, Ishak (Praise Worthy Prize S.r.l., 2011)
Link to publisher's homepage at http://www.praiseworthyprize.com